The problem of loneliness in a situation of compulsory isolation a condition for the development of depressive mental states in student youth (Actual Problems of Psychology in Educational Institutions, 2021)
The article reveals the phenomenology of loneliness anddepression, studies the main forms, levels of manifestation of thesephenomena, the conditions for their occurrence and development, featuresof manifestation in student youth. It was found that the situation ofcompulsory isolation leads to an increase in the level of loneliness, depressionand, as a result, can negatively affect the psychological health of youngpeople. It has been statistically proven that loneliness in a situation ofcompulsory isolation can be considered as a factor in the development ofdepressive mental states, the occurrence of depresive disorders. The spreadof depressive mental states was noted.
Keywords: loneliness, compulsory isolation, depressive mental states, a young adult, student